STUDY OF PLUTONIUM UTILIZATION IN AP1000 REACTOR USE SRAC2006 AND JENDL 3.3 NUCLEAR DATA LIBRARY - Nailatussaadah Nailatussaadah; Abdul Waris; Puguh Andik Prastyo (HIMNI, 2022)
Preliminary Study of Plutonium Utilization in AP1000 Reactor Use SRAC 2006 and JENDL 3.3 has been conducted. Nuclear energy, especially for nuclear reactor, become important this day because the need of energy will increase along with the increasing of human population, the advanced technology and economic. The more nuclear reactor operated the more existence of plutonium stockpile. This study evaluated the standard of Westinghouse AP1000 reactor and ZrB2 as Integral Fuel Burnable Absorber (IFBA). Different fuel compositions of assembly type were analyze in by using SRAC 2006 code system with JENDL 3.3 nuclear data library. This study aiming to compare the neutronics characteristics of an UO2 and an (U,Pu)O2 assembly designs. Some results of the study show that optimal criticality of the fuel assembly can be accomplished by using 5% enrichment of U-235 for UO2 fuel and 9% plutonium fraction for (U,Pu)O2 fuel assembly.